Consumers Behind Solar Energy: A Case Study of Households’ Demand for Four OECD Countries - Mozayeni, Simin; Pillai, Unni; Wang, Rui (Journal of Strategic Innovation and Sustainability, 2019)
We investigate households’ demand for solar energy in France, Germany, Italy and US, using a loglinear demand for each, and a combined panel data, with fixed effects, for 2000-2012. The dependent variable is household’s installed solar panels; whereas the independent variables are income, price of solar panels, interest rate, representing the cost of financing of a project, and price of “traditional energy.” With R2 being 0.9, all coefficients having expected theoretical signs and statistical significance in all specifications, our model can be generalized for other countries’ households’ solar demand. This is a major contribution to the theoretical and empirical literature.